Pengaruh Suhu dan Waktu pada Kadar Gula Siwalan Cair - M. Zaki Hasim (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2025)
This study aims to analyze the effect of temperature variations and heating duration on the sugar content of liquid Siwalan (Palmyra palm) sugar. Sugar content is a critical parameter in determining the quality of processed palm sap products. The research method utilized an experimental design with two factors: heating temperature (100°C, 115°C, 125°C) and heating duration (1 hour, 2 hours, 3 hours). Data were analyzed using descriptive and inferential statistics (Two-Way ANOVA) after fulfilling the classical assumption tests of normality and homogeneity.The results showed that the sugar content of liquid Siwalan sugar ranged from 43.33 to 81.67 °Brix. The two-way ANOVA results confirmed that the temperature factor had a significant effect on sugar content 0.004, while the time factor 0.227 and their interaction 0.556 did not have a significant effect. Duncan's multiple range test showed that the 100°C treatment was significantly different from 115°C and 125°C, but there was no significant difference between 115°C and 125°C. Heating beyond the optimal point, particularly at a duration of 3 hours, tends to decrease sugar content due to thermal degradation through Maillard reactions and caramelization. The optimal condition was obtained at a temperature of 125°C with a heating duration of 2 hours, yielding the highest sugar content of 81.67 °Brix. Precise operational temperature control is a key factor in maintaining the efficiency and quality of liquid Siwalan